Neurobiological mechanisms of motor and motivation deficits of dopamine - Stasny, Petr; Petr, Miroslav; Rzeszutko-Polak, Agata; Niewczas, Marta; Król, Paweł; Czarny, Wojciech; Niewczas-Czarny, Patryk; Chmielowiec, Jolanta; Masiak, Jolanta; Trybek, Grzegorz; Moska, Waldemar; Gronek, Joanna; et al. (Akademia Wychowania Fizycznego w Poznaniu)
Dopamine (3,4-dihydroxyphenethylamine) together with adrenaline and noradrenaline belong to the group of catecholamines present in different tissues, predominantly in the nervous system, where they function as neurotransmitters. Our choice of the genetic determinants of the dopaminergic system disorders for the main topic of our project study was influenced by a wide spectrum of influence which the system has on the functions of an organism connected with, for example, its adaptive response to physical effort (it is the very adrenergic system that physiologists call the “work and fight” and even the “fight and flight” system). It is, for example, proven by the confirmed influence of dopaminergic mechanisms on blood pressure, widening of bronchi and a mobilization of energetic substrates. On the other hand, it is worth mentioning another importance of dopamine recognized by psychologists and psychiatrists as the hormone of “motivation, thrill and adventure seeking”, which in sport can be of key importance. That is why we would like to link these two areas – genetic and psychological
Keywords: dopamine; sports; motivation; reward system; methylation